Pro-angiogenic Activity of Notoginsenoside R1 in Human Umbilical Vein Endothelial Cells in vitro and in a Chemical-Induced Blood Vessel Loss Model of Zebrafish in vivo - 杨彬睿 洪思佳 李铭源 丛伟红 万建波 张哲睿 张庆文 张燚 王一涛 林志秀 (Chinese journal of integrative medicine, 2016)
Objective： This study aimed at investigating whether notoginsenoside R1 （R1）, a unique saponin found in Panax notoginseng could promote angiogenic activity on human umbilical vein endothelial cells （HUVECs） and elucidate their potential molecular mechanisms. In addition, vascular restorative activities of R1 was assessed in a chemically-induced blood vessel loss model in zebrafish. Methods： The in vitro angiogenic effect of R1 was compared with other previously reported angiogenic saponins Rgl and Re. The HUVECs proliferation in the presence of R1 was determined by cell proliferation kit lI （XTI＇） assay. R1, Rgl and Re-induced HUVECs invasion across polycarbonate membrane was stained with Hoechst-33342 and quantified microscopically. Tube formation assay using matrigel- coated wells was performed to evaluate the pro-angiogenic actions of RI. In order to understand the mechanism underlying the pro-angiogenic effect, various pathway inhibitors such as SU5416, wortmannin （wort） or L-N （o -nitro- L-arginine methyl ester hydrochloride （L-NAME）, SH-6 were used to probe the possible involvement of signaling pathway in the R1 mediated HUVECs proliferation. In in vivo assays, zebrafish embryos at 21 hpf were pre-treated with vascular endothelial growth factor （VEGF） receptor kinase inhibitor ]1 （VRI） for 3 h only and subsequently post-treated with R1 for 48 h, respectively. The intersegmental vessels （ISVs） in zebrafish were assessed for the restorative effect of R1 on defective blood vessels. Results： R1 could stimulate the proliferation of HUVECs. In the chemoinvasion assay, R1 significantly increased the number of cross-membrane HUVECs. In addition, R1 markedly enhanced the tube formation ability of HUVECs. The proliferative effects of these saponins on HUVECs were effectively blocked by the addition of SU5416 （a VEGF-KDR/FIk-1 inhibitor）. Similarly, pre-treatment with wort [a phosphatidylinositol 3-kinase （PI3K）-kinase inhibitor], L-NAME [an endothelial nitric oxide synthase （eNOS） inhibitor] or SH-6 （an Akt pathway inhibitor） significantly abrogated the R1 induced proliferation of HUVECs. In chemically- induced blood vessel loss model in zebrafish, R1 significantly rescue the damaged ISVs. Conclusion： R1, similar to Rgl and Re, had been showed pro-angiogenic action, possibly via the activation of the VEGF-KDR/FIk-1 and PI3K- Akt-eNOS signaling pathways. Our findings also shed light on intriguing pro-angiogenic effect of R1 under deficient angiogenesis condition in a pharmacologic-induced blood vessels loss model in zebrafish. The present study in vivo and in vitro provided scientific evidence to explain the ethnomedical use of Panax notoginseng in the treatment of cardiovascular diseases, traumatic injuries and wound healing.